Conflict Management: A Systematic Literature Review (SLR) - Saqif Haidarravy; Mochammad Isa Anshori (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
The purpose of ithis literature review is to find and examine various definitions of conflict management based on the broad context of previous research. This research was conducted qualitatively using the literature study method with the help of the Google Scholar and Mendeley databases. The type of data iused in this literature review is a type of secondary data in the form of articles and research journals totaling 29 articles and research journals both nationally and internationally with the journal publication year 2011-2022. The results of this literature review are based on the results of bibliometric data analysis through the context of previous research which shows that there are 5 definitions of conflict management, there are 4 antecedents of conflict management and there are 6 consequences of conflict management, there iare 9 sectors of conflict management